Capturing the untold: photography as a tool for empowering children to interpret their embodied experiences in museums. Issue 3 (2nd October 2017) - Kalessopoulou, Despina
Abstract: Children's museums and exhibitions designed for children are well-thought adult projects; however, children rarely participate in the design process. Visual research methods can provide a remedy for this scarcity of children's agency in determining significant exhibition qualities. The paper will discuss a visual research methodology that empowers children, even very young ones, to express their opinion in a palpable and child-friendly way on what is important for them in the exhibition design of child-centred museums, while at the same time sensitizing them to the importance of visual images in conveying messages. Equipped with a digital camera 60 children ranging from the age of 4–12 years old captured the elements that were of special notice to them during their visit; images were later used as a prop in analysing their embodied experience, based on the content, the angle and framing of the photographs, as well as children's own selection criteria. Apart from presenting the main findings concerning the qualities of the exhibition space that emerged as significant from the children's perspectives, the article draws special attention to issues related to the use of camera with regard to the age of children, the contribution of photography in capturing the physicality of their experience, and the challenges that the research context sets for visual data production and analysis.